Albania Between Italy and the First Balkan Conference 1930 - Shahini , Anduana (KÃ«rtalli) (Mediterranean Journal of Social Sciences, 2012)
The period between two World Wars brought a new political atmosphere between countries. The Balkans, in foreign andinternal policy, is part of these changes. Albania, being part of the region, was involved in social â€“ economic changes and also politicalthat occurs within it. The Balkans tentative for unification came in early 1930 and exactly in First Balkan Conference, to create a BalkanLocarno. Albania's participation comes at a difficult economical and political moment. Its external ally, Italy, thought to repeat bilateralpacts. Which will be the position of Albania, the impact that will create its participation, and the results obtained, will be examinedthrough the research in the central archives of the Albanian state and archives of the Ministry of Foreign Affairs of Albania and thecentral library for periodicals of the years 1930-1934 in Tirana.